Implementasi Program Sistem Perizinan Online (SPION) Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Sukoharjo - Mulat Tri Purwani; Retno Suryawati (Program Studi Ilmu Administrasi Negara Fakultas Ilmu Sosial dan Politik Universitas Sebela, 2021)
This study aims to determine the factors that influence the implementation of the SPION Program at the Investment Service and One Stop Services in Sukoharjo Regency.This research is a qualitative descriptive study conducted at the One Stop Investment Service and One Stop Services in Sukoharjo Regency. Data obtained through interviews with purposive techniques, documentation and observation which were analyzed using the data analysis model by Miles and Huberman. The results of this research showed that the implementation of the SPION Program at the Investment Service and One Stop Services (DPMPTSP) in Sukoharjo Regency has been going well. The factors that drive the implementation of the SPION Program at the One Stop Investment Service and Integrated Services in Sukoharjo Regency are the factors of resources, disposition, and bureaucratic structures. While the factors that hindered the implementation of the SPION Program at the One Stop Investment and Integrated Service Office (DPMPTSP) in Sukoharjo Regency were communication factors, such as limited people invited to socialization activities, limited budgets for socialization activities, and now people rarely have and listen to the radio. This is what causes the public's disregard for the existence of the SPION Program and the lack of public understanding of the licensing service procedures through the SPION Program so that the people of Sukoharjo Regency prefer to come directly to the Office of Investment and One Stop Integrated Services (DPMPTSP) in Sukoharjo Regency to ask for assistance to service officers assisted in applying for licenses online through the SPION Program.